Feeding, growth and chemical control of hog-plum beetle (Podontia 14- punctata) - Khatun, Mousumi; Uddin, Mohammad Mahir; Haque, Md Azizul; Rhaman, Mohammad Saidur (Research in Agriculture Livestock and Fisheries, 2016)
Experiments were conducted to study the feeding, growth and chemical control of hog-plum beetle (Podontia 14-punctata) in the laboratory and in the field. It was found that larval leaf consumption gradually increased with the increase of age of larva. Mean leaf consumption per larva was 0.28g, 0.86g and 1.70g after 24, 72 and 144 hrs, respectively. Growth pattern of larva was depended on the rate of leaf consumption. The average body weight of larvae was increased with time and per larva was recorded as 0.06g, 0.19g and 0.45g after 24, 72 and 144 hrs of leaf consumption. Daily leaf consumption was higher in adults than larvae. Mean leaf consumption per adult was 0.24g, 0.91g and 1.87g after 24, 72 and 144 hrs, respectively. Mortality of larvae and adults against four chemical insecticides viz. Altima 40WG, Belt 24WG, Libsen 45SC and Limper 10EC were observed both in the laboratory and field. All the treatments had a significant effect on mortality percentage of larva and adult in comparison to control. The highest mortality percentage of the larva (86.67) and adult (80.00) were observed in the case of Limper 10EC at 72 hrs after spraying. However, there was no significant difference observed in efficacy among Limper 10EC, Belt 24WG and Libsen 45SC. In field, percentage of leaf protection over control after 1st spray was the highest (37.95) in Limper 10EC and the lowest (20.86) in Altima 40WG treated plants. The results of laboratory and field trials revealed that Limper 10EC might be recommended for effective control of P. 14-punctata. Res. Agric., Livest. Fish.3(3): 387-394, December 2016